Assessment on water quality for residential building in Klang Valley / Muhamad Amer Zakaria - Zakaria, Muhamad Amer (Faculty of Architecture, Planning and Surveying, 2013)
This research has been made of this is a study on the assessment of water quality in residential buildings in the Klang Valley. This research has four objectives to assess water quality for residential buildings in the Klang Valley such as to understand the standard of water quality supply to building or consumer, to investigate the causes of poor water quality in buildings, to analyze the contained of sample water taken from supply system in building and to give recommendation for the solution to the problem of poor water quality in building. The study was conducted using informal interviews and laboratory testing of certain parameters. The six samples of water quality laboratory tested based on the parameters set by the Jabatan Bekalan air (JBA), Kementerian Kesihatan Malaysia and Worth Healthy Organization (WHO). The results of laboratory tests indicate that the of each parameter standard are high in each buildings. It show that the quality of water in residential buildings in Klang Valley less safe to use for daily activities. It can be detrimental to human health. To address this concern, some suggestions are made to reduce the problem of water quality and ensure water qualities in residential buildings are safe and protected from any contamination.